1H 0707‐495: An AGN is dimming its X‐ray light. Issue 5 (7th July 2021) - Boller, Thomas
Abstract: We report on one of the first science observations obtained during the Calibration and Verification phase of extended ROentgen Survey with an Imaging Telescope Array (eROSITA) aboard the Spectrum‐Roentgen‐Gamma (SRG) mission on the famous Narrow‐Line Seyfert 1 Galaxy 1H 0707‐495. 1H 0707‐495 is a highly variable AGN, with a complex, steep X‐ray spectrum, which has been the subject of intense studies with XMM‐Newton in the past. During the eROSITA observations, 1H 0707‐495 showed a dramatic flux drop in about 1 day. The source is brightest at the beginning of the observations, with rapid fluctuations in count rate, followed by a subsequent decline in count rate going down close to the background level. The mean amplitude variability is a factor of 58, with a 1 σ error confidence interval with factors between 31 and 235. Similar, large‐amplitude count‐rate changes are deduced from the XMM‐Newton EPIC‐pn and MOS2 light curves. The energy band up to only 0.8 keV is dominating the amplitude variability, followed by a sudden drop in variability above 0.8 keV. Such extreme ultrasoft and large‐amplitude flux variability in active galactic nuclei has not been detected with other X‐ray observations so far. A physical explanation for the timing and spectral properties is a combination of strong relativistic effects close to the black hole and absorption by an ionized partial coverer. From the high‐ to the low‐flux state, the partial coverer is obscuring an increasing part of the emitted X‐ray radiation. Ionized outflowing absorbers are more transparent in the soft X‐rays than neutral absorbers and thus show leakage effects in the soft X‐rays, explaining the ultrasoft light curve.